A model of energy dissipation at fatigue crack tip in metals - Oleg Plekhov; Aleksei Vshivkov; Anastasia Iziumova; Balasubramaniam Venkatraman (Fracture and Structural Integrity)
Experimental and numerical studies investigating fatigue crack growth were conducted on flat samples made of stainless steel AISE 304 and titanium alloy Grade 2. The heat flux from the crack tip caused by plastic deformation localization was measured using the contact heat flux sensor previously developed by the authors. This provides a possibility to find a correlation between energy dissipation and crack propagation rate under fatigue uniaxial loading with constant stress intensity factor and under biaxial loading with constant stress amplitude. The experiments with constant stress intensity factor have shown a decrease in energy dissipation at constant crack rate and stress ratio R=smin/smax=-1 (R=0). A theoretical analysis of the stress field at the fatigue crack tip has been carried out to explain this phenomenon. Based on the obtained results, the heat flux from the crack tip is represented as the sum of two functions describing energy dissipation in monotonic and reversible plastic zones separately. It has been shown that dissipation in a reversible plastic zone is a function of the applied stress amplitude only. This causes a decrease of energy dissipation at constant stress intensity factor. The proposed phenomenology was successfully verified by testing both materials under biaxial loading.